Improvement of English Grammar Understanding Using ERWRT For STMIK STIKOM Indonesia’s Students - Maria Osmunda Eawea Monny; Evelyn Angelita Pinondang Manurung (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
This study aims to improve English grammar understanding using ERWRT for STMIK STIKOM Indonesia’s students. The approach in this research is action research using Classroom Action research (CAR). The data are collected by using observation, interview and literary research. The results of this study showed that the implementation of ERWRT has improved students’ level of understanding on English grammar that can be seen through pre-implementation, Middle Test (Cycle I) and Final Test (Cycle II). The results of pre–implementation show that out of 38 students, there were 28 students did not get the lowest score 55 as the passing score of the college. Middle Test (Cycle I) tested 6 topics those are (1) subject pronouns; (2) preposition of place; (3) simple present tense; (4) agreement of subject and verb; (5) agreement of numbers and nouns dan (6) simple past tense. The results of the test show that out of 36 students only 18 students get the score above 55. Final Test (Cycle II) there is 15 numbers tested with 6 previous topics and 6 new topics; those are (1) article; (2) object pronouns; (3) time division (AM/PM); (4) telling time and (5) modal verbs. The results of Cycle II show that 35 students can score above 55. In conclusion, ERWRT can be applied to improve students’ level of understanding on English grammar and writing skills. This test also can be used to analyze grammar error through reading but cannot be used for listening and speaking skills.